Epidemiology and Risk Factors of Esophageal Cancer - Sunpaweravong, Somkiat (The Thai Journal of Surgery, 2010)
Esophageal cancer is the eighth most common malignancy in the world. In general, squamous cell carcinoma is more common than adenocarcinoma, except in the USA. The etiology of the cancer is multifactorial, involving such things as smoking, alcohol, dietary habits, viral infections, GERD, environmental carcinogens, and socioeconomic status. This review also shows factors that may protect against the development of esophageal cancer such as a diet rich in fruits and vegetables or consumption of NSAIDs or helicobactor pylori infection in adenocarcinoma.